The structure of viral hepatitis and dynamics of cytolitic syndrome in patients with oncohaematological diseases - T. V. Antonova; M. S. Nozhkin; E. Yu. Karnaukhova; L. S. Zubarovskaya (Журнал инфектологии)
The aim of the research. Evaluation of the structure of viral  hepatitis in patients with oncohaematological diseases and activity of ALT and AST during various methods of treatment of the main disease.Materials and methods. Retrospective analysis of data from 2000  patients treated during 2001–2014 in Raisa Gorbacheva Memorial  Research Institute for Pediatric Oncology, Hematology and  Transplantation Pavlov of the First Saint Petersburg State Medical  University was carried out. The dynamics of cytolytic enzymes during therapy (polychemotherapy, transplantation of hematopoietic stem  cells, symptomatic) of oncohematological diseases was evaluated between the patients with concomitant chronic viral  hepatitis (N=175) and without liver pathology (N=203). Analysis was performed with SAS software. Results. Over a 10-year follow-up period, 9% of the oncohematological patients of the specialized center identified markers of hemocontact viral hepatitis. The results of the study  showed that in patients with concomitant viral hepatitis, in contrast  to a group without hepatitis the activity of ALT and AST significantly  increased compared to baseline values after the treatment of  hematological malignancy. It was twofold increase of the activity of  enzymes after transplantation of hematopoietic stem cells and 3–4- fold incease after courses of polychemotherapy. In patients without  viral hepatitis, changes in enzyme activity after such therapy were  not observed. Summary. Thus, the associated effect of concomitant viral hepatitis  and toxic effects of treatment methods with the use of  polychemotherapy and transplantation of hematopoietic stem cells  was proven on the development of cytolytic syndrome in oncohematological patients.